A Comparative Study of Breast Cancer Screening by Age Across 10000 Tunisian Women - Daoud, Jamel; Ben Kridis, Wala; Elloumi, Fatma; Ayedi, Inès; Mnejja, Wafa; Yaiche, Ouhoud; Frikha, Mounir (Reviews on Recent Clinical Trials, 2016)
Introduction: We propose in this study to analyze the results obtained in the experience of Dar El Amal by comparing the two age groups 45-49 years versus over 50 years. This experience of Dar Al Amal was started in Sfax (Tunisia) in 2004. The project had included women over a period of six and a half years. The target population was all women over the age of 45 years. Results: In the period of the study, 10 000 women had at least one mammography within the first round in Dar El Amal. The average age was 51.56 years. The recall rate was more important in women aged 45-49 years compared with those over 50 years with a statistically significant relationship (p=0.013). Tests classified ACR0 and ACR3 predominated in women aged between 45 and 49 years with a statistically significant relationship. The positive predictive value (PPV) of mammography was better in those over 50 years (p=0.012). Conclusion: The majority of countries in the world opt for screening from the age of 50 years. Women under 50 years are not routinely concerned, but they have more right to a targeted and appropriate screening.
Keywords: mammography